Calcitonin in bone-guided regeneration of mandibles in ovariectomized rats: densitometric, histologic and histomorphometric analysis - Arisawa, E. A. L.; Brandão, Adriana Aigotti Haberbeck [UNESP]; Almeida, J. D. [UNESP]; da Rocha, R. F. [UNESP] (Churchill Livingstone, 2008)
The aim of the present study was to investigate bone promotion in surgical defects created in the mandible of normal and ovariectomized female rats using calcitonin associated with a polytetrafluoroethylene barrier. The 100 female rats were divided into four groups: control (C), control treated with calcitonin (CM), ovariectomized control (OV) and ovariectomized treated with calcitonin (OVM). A circumscribed bone defect 4 mm in diameter was created in the region of the mandibular angle, and covered with the barrier. Groups CM and OVM received 2 IU/kg of synthetic salmon calcitonin intramuscularly three times a week. The animals were killed 3, 7, 14, 21 and 28 days after surgery. The bone defects were submitted to densitometric, histologic and histomorphometric analysis. Groups C and CM showed higher levels of bone formation after 7 days compared to the OV and OVM groups. A significant difference was observed between groups C and OV at 3-14 days. The OV group presented slower bone regeneration of the surgical bone defect created in the mandibular angle than group C. Synthetic salmon calcitonin accelerated regeneration of the bone defect in the mandibles of OVM animals similarly to group C, and also increased the formation of new bone during the regeneration process in CM.
Keywords: calcitonin; mandible; bone regeneration; bone density; osteoporosis; postmenopausal; osteogenesis